HUACHOS, PELUSAS, THIEVES AND BUGS: JUVENILE DELINQUENCY. TEMUCO 1929-1943 - Cárcamo Hernández, Ovidio (Revista de Historia Social y de las Mentalidades, 2025)
this paper it is centred in the typolo- gical research about minors who had judiciary problems in a period included from the years 1929 to 1943 in temu- co city and its surrounding. on the other hand it is an study which we can recognize as a process leading to the criminalization of the lower classes of our society led by the elites who have had the support of the judiciary and criminalist theories in order to get this end. For this purpose we describe the socio-economic characteristic of the teenagers who were processed and at the end we described the process of punis- hment and re-education this adolescent were submitted within the state of law.